Geometric Aspects of the Painlevé Equations PIII(D₆) and PIII(D₇) - Marius van der Put; Top, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2014)
The Riemann-Hilbert approach for the equations PIII(D6) and PIII(D7) is studied in detail, involving moduli spaces for connections and monodromy data, Okamoto-Painlevé varieties, the Painlevé property, special solutions and explicit Bäcklund transformations.